2019
DOI: 10.1371/journal.pone.0224987
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors affecting dairy cattle protective grouping behavior, commonly known as bunching, against Stomoxys calcitrans (L.) on California dairies

Abstract: Bunching is the term used to describe the protective aggregating behavior of cattle against the painful bites of stable flies (Stomoxys calcitrans), where cattle gather in a group with their heads to the center of the group and their tails to the outside to reduce stable fly attack. Both sexes of the stable fly feed on blood, and their painful bites negatively impact cattle health, productivity and welfare. A longitudinal study was conducted from April to July 2017 to estimate the stable fly activity on 20 Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Group-level responses in a potentially threatening situation are one of the benefits of group-living (43). Other research has shown cattle will act as a coordinated group in their patterns of avoiding biting pests (44,45). In the case of the VF, the stimuli are initially highly unexpected with no visual cues and a benign audio tone as a warning for the electrical pulse.…”
Section: Discussionmentioning
confidence: 99%
“…Group-level responses in a potentially threatening situation are one of the benefits of group-living (43). Other research has shown cattle will act as a coordinated group in their patterns of avoiding biting pests (44,45). In the case of the VF, the stimuli are initially highly unexpected with no visual cues and a benign audio tone as a warning for the electrical pulse.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fans can produce noise that may annoy the cows or may be installed to repel biting insects. Grouping behavior of cows as a result of biting stable flies has been observed in California and described by El Ashmawy et al (2019). Interestingly, relative to control farms, the case farms more often mentioned a high burden of flies but less often applied insecticides or applied only nonchemical insecticides (Table 3; P ≤ 0.10), but these factors were not retained in the final multivariable model.…”
Section: Discussionmentioning
confidence: 94%
“…They hypothesized that avoiding heat as well as stinging insects might be the cause of this behavior. Stinging insects are known to cause grouping behavior of cattle, known as bunching (El Ashmawy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Data for this research was part of a larger study that investigated the epidemiology of cattle bunching [16]. Briefly, the current study data were collected from 20 dairies in Tulare and Kings Counties between April 26 th , 2017 and July 31 st , 2017.…”
Section: Study Design and Herdsmentioning
confidence: 99%
“…Bunching can contribute to reduced feed intake, weight gain, and milk production by individual cattle [15]. Cattle bunching is positively associated with the number of stable flies biting cattle on the front legs [16]. The estimated average loss to U.S. cattle industries induced by Stomoxys calcitrans was $2.2 billion per year in 2009, with $360 million lost from the dairy industry alone [4].…”
Section: Introductionmentioning
confidence: 99%